Makrozoobenthos Sebagai Indikator Biologis Tingkat Pencemaran Muara Sungai Rokan Provinsi Riau - Yusmidar Yusmidar; Madju Siagian; Asmika Harnalin Simarmata (Berkala Perikanan Terubuk, 2015)
Aimed this study was assess the level of pollution Rokan estuary using macrozoobenthos as bio-indicators, assess the level of pollution of water quality in Rokan estuary and examines the relationship between macrozoobenthos of water quality in Rokan estuary. This study was conducted in September 2014 in Rokan estuary. Location of sampling consisted of four stations namely ST 1 in the village of Pekaitan, ST 2  between the village of Pekaitan and the village of Sungai Panji - Panji, ST 3 in the village of Sungai Panji - Panji and ST 4 in the village of West Bagan. Samplings were conducted three times, once per week at high tide and low tide. This research used survey method and data analysis using BBI and AMOEBA method. The results of this study indicate that the pollution level of Rokan estuary by macrozoobenthos as bioindicator were heavily polluted, where as based on water quality were light polluted to moderate polluted.